Keefektifan Pemberian Bimbingan Spiritual Islami Kepada Klien Terminal terhadap Kecemasan dan Motivasi Hidup di Rumah Sakit Umum PKU Muhammadiyah Yogyakarta - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
Background: This study was done to evaluate the effectiveness of Islamic Spiritual support done by Bina Rohani (BRI) on the terminally-ill patients in terms of anxiety and live motivation. The outcome being observed was willingness to earn money, motivation to work and compliance. Purpose of the study: The purpose of study was to evaluate the effectiveness of Islamic spiritual support on the terminally ill patient in terms of anxiety and life motivation with observing willingness to earn money, motivation to work and compliance. Method: The study design used was pre and post-test quasi experiment. The patient included 67 respondent, consisting of 35 exposed and 32 control groups. The expand group was treaded by Bina Rohani Islam (BRI) using standard guidance developed by the hospital. The control group were those who did not received such a treatment. Result and Conclusion: The result showed that the treatment decreased the level anxiety significantly compared to the control group increased live motivation significantly. The result show that there was a decrease in the level of anxiety average from 475 in pretest to posttest 1=50 and posttest 2=53,8. Meanwhile, the control group did not show changes significantly. The study concluded that Islamic spiritual support decreased the level of anxiety and increased life motivation significantly. The investigator suggested the use of this instrument to all term ill patientito support the lives. Availability of health promotion staff to arrange the protocol for spiritual support in PKU Muhammadiyah hospital in needed.